Proportion of mangrove growth stages in selected sites in the Provinve of Antique, Panay Island, Philippines. - Montales, Barbara Lyra Arnaldo
No study has been conducted to document the proportion of mangrove growth stages in Antique, panay island, Philippines. This study will provide adequate information needed for the proper utilization and management of mangroves in the area. This study determines the proportion of various mangrove growth stages in selected sites and specifically determines the density of trees, seedlings and saplings of mangrove per species, per municipality and per species among sites. The area consisted of eleven municipalities: Anini-Y, Hamtic, San Jose, Belison, Patnongon, Bugasong, Barbaza, Tibiao, Culasi, Pandan, and Caluya. Sampling period was from December 2005 to February 2006. The Transect Line Plot method was used for sampling. Nypa fruiticans had the highest tree density with 162,500.710 and Avicennia marina for saplings and seedlings with 20,266.957 and 35,636.277, respectively. Among the 11 municipalities, Anini-y had the highest tree, seedling and sapling density with 85352.381, 23614 and 59202.381, respectively. Nypa fruiticans in Hamtic had the highest tree density per species among all sites with 38,744.058, Avicennia marina in Anini-y for saplings with 18,261 and still A. marina in Anini-y with a density of 28,619.048. Seedlings and saplings are components of the angrove cover that is important to the equilibrium of a mangal. The various growth stages are affected by factors such as stand structure, natural disturbances and canopy gaps. This study will provide helpful information for researchers in knowing which areas are in need of preservation. This will also benefit mangrove users, in the proper protection and future management of the remaining mangroves.